Micarea fennica, a new lignicolous lichen species from Finland - Launis, Annina; Myllys, Leena (Phytotaxa, 2019)
A new species Micarea fennica is described based on phenotypic and molecular features. The species is characterized by a pale olive green, bright green or greyish green minutely granular thallus composed of goniocysts, and stalked pycnidia that are dark grey to dark brown with Sedifolia-grey pigment in the wall structures (K+ violet, C+ violet), 0.2–0.5(–1) mm tall and covered by a thin white tomentum. The species produces micareic acid. Micarea fennica is similar to M. hedlundii and M. botryoides, but differs by having a paler granular thallus, stalked dark grey to dark brown pycnidia covered by a thin white tomentum and the production of micareic acid. The new species occupies soft lignum of late decay stages and is probably rare.